Baseline physical activity is associated with reduced mortality and disease outcomes in COVID‐19: A systematic review and meta‐analysis. (13th April 2022) - Rahmati, Masoud; Shamsi, Mahdieh Molanouri; Khoramipour, Kayvan; Malakoutinia, Fatemeh; Woo, Wongi; Park, Seoyeon; Yon, Dong Keon; Lee, Seung Won; Shin, Jae Il; Smith, Lee
Abstract: Among coronavirus disease 2019 (COVID‐19) patients, physically active individuals may be at lower risk of fatal outcomes. However, to date, no meta‐analysis has been carried out to investigate the relationship between physical activity (PA) and fatal outcomes in patients with COVID‐19. Therefore, this meta‐analysis aims to explore the hospitalisation, intensive care unit (ICU) admissions, and mortality rates of COVID‐19 patients with a history of PA participation before the onset of the pandemic, and to evaluate the reliability of the evidence. A systematic search of MEDLINE/PubMed, Cumulative Index to Nursing and Allied Health Literature, Scopus, and medRxiv was conducted for articles published up to January 2022. A random‐effects meta‐analysis was performed to compare disease severity and mortality rates of COVID‐19 patients in physically active and inactive cases. Twelve studies involving 1, 256, 609 patients (991, 268 physically active and 265, 341 inactive cases) with COVID‐19, were included in the pooled analysis. The overall meta‐analysis compared with inactive controls showed significant associations between PA with reduction in COVID‐19 hospitalisation (risk ratio (RR) = 0.58, 95% confidence intervals (CI) 0.46–0.73, P = 0.001), ICU admissions (RR = 0.65, 95% CI 0.52–0.81, P = 0.001) and mortality (RR = 0.47, 95% CI 0.38–0.59, P = 0.001). The protective effect of PA on COVID‐19 hospitalisation and mortality could be attributable to the types of exercise such as resistance exercise (RR = 0.27, 95% CI 0.15–0.49, P = 0.001) and endurance exercise (RR = 0.41, 95% CI 0.23–0.74, P = 0.003), respectively. Physical activity is associated with decreased hospitalisation, ICU admissions, and mortality rates of patients with COVID‐19. Moreover, COVID‐19 patients with a history of resistance and endurance exercises experience a lower rate of hospitalisation and mortality, respectively. Further studies are warranted to determine the biological mechanisms underlying these findings.